Opintotukijärjestelmän uudistaminen: Rakenteelliseen malliin perustuvia vaikutuslaskelmina; Reforming Student Financial Aid – Estimates from a Structural Model - Hannu Karhunen; Niku Määttänen; Roope Uusitalo (The Research Institute of the Finnish Economy (ETLA), 2016)
– We analyse how alternative reforms of the student financial aid would influence average study duration, government expenditures, and tax revenues. We also consider the reform that has been proposed by the current government (in 2016) which consists of lowering the monthly student grant and decreasing the maximum eligibility period while increasing the maximum study grant. Our results are based on a structural model that describes the financial constraints and incentives faced by the students. The model is calibrated with register based panel data on students' study progress, withdrawal of study grants and student loans, and wage income. According to the results, the reform proposed by the current government will reduce government expenditures on student aid by about 20 percent, which is close to the government's target. However, the reform is also likely to increase the average study duration. The size of this effect depends on how willing the students are to take student loans.
Keywords: D14; H24; J22; 330; Student financial aid; Study duration; Studienfinanzierung; Studium; Dauer; Bildungspolitik; Wirkungsanalyse; Finnland